Protección fitosanitaria del arbolado urbano en San José, Costa Rica (Repertorio Científico, 2021)
Green spaces in cities, including trees serve multiple functions for the benefit of society. Generally, trees in the city are under unfavorable conditions for their health, reducing its vigor and many of them are sick. To handle any phytosanitary problem, it is necessary to make a diagnosis that clearly identify their causes. This paper describes the main phytosanitary problems detected in the city of San José (Costa Rica), produced by biotic agents such as insects, mites, fungi, bacteria and mistletoes and other limiting factors for the development of trees.
Keywords: Key Words: Arboriculture, Pests, Diseases, San José, Costa Rica